Sustainable livelihoods approaches to inform government‐local partnerships and decision‐making in vulnerable environments. (21st February 2019) - Edwards, Peter; Sharma‐Wallace, Lisa; Barnard, Tim; Velarde, Sandra J.; Warmenhoven, Tui; Fitzgerald, Gerard; Harrison, Duncan; Garrett, Loretta; Porou, Tina; Pohatu, Pia
Abstract : Sustainable livelihoods approaches used in international development are applied to a vulnerable New Zealand catchment. The Waiapu Catchment has a high proportion of indigenous residents, and is one of the most remote and deprived areas in the country. Linear and centralised approaches to indigenous development have failed to bring about desired changes. We identify "capitals" (social, human/political, physical, natural, financial and cultural) present in the catchment. From this assessment, we propose capital‐based holistic approaches to bring about community‐led change. The assessment and resulting approaches can be used in other vulnerable environments around the world.